The effect of positional release therapy on intercollegiate male basketball athletes classified with patella tendinopathy - Bianco, L. C.; May, J. M.; Fermin, S. L.; Oates, R.; Cheatham, S. W. (International Journal of Athletic Therapy & Training, 2019)
In the current case series, three male patients aged 19-21 years, all participating in basketball activities during their competitive season, were evaluated and classified with patella tendinopathy. A combination of positional release therapy (PRT) treatment with therapeutic exercises was used to decrease pain and improve function. Over the course of the treatment, each patient improved outcomes at discharge and sustained the improvements at follow-up. The purpose of this paper is to compare the results of this case series with a study of the effects of eccentric exercises on physically active patients diagnosed with patella tendinopathy and participating in jumping sports.